Pengujian Black Box Dengan Teknik Transition Pada Sistem Informasi Perpustakaan Berbasis Web Dengan Metode Waterfall Pada SMC Foundation - Mintarsih Mintarsih (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Black box testing is so important because the technique is able to identify errors in functions, interfaces, information models and access to outside information sources. In the implementation often arises the problem of testers not being sure whether the software being tested has actually passed the testing stage. This happens because there may still be some untested execution paths. Testers should create every possible combination of input information for the test. Choosing input information to find errors is a problem for testers because it has a high probability, so the test case design can automatically be a solution. In this implementation, the web that will be tested using black-box testing is a Library Information System. The SMC Library website will be tested using black-box testing where the test only aims to see if the program is in accordance with the desired function of the program. This method is done by looking at the inputs and outputs of each system flow. Testers in this test method do not have to understand the flow of system code, but must know the flow of system expectations. One of the techniques of the black box testing method is the state transition technique. The state transition technique is performed by looking at the suitability of the flow from one pipeline to the next